História, cultura e música em Belém: décadas de 1920 a 1940 - Corrêa, Ângela Tereza de Oliveira (2010)
This investigation is focused in Belém, Pará, between the 1920s and 1940s. Under the perspective of Cultural History, it seeks to recover other urban experiences and sonority. In a moment of economic and cultural changes, the intellectuals from Pará attempt to delineate new faces for the city, making it acquire more regional contours. Instead of Paris in l America, as the elites liked to call it, it was called brunette city, city of the mango trees, of the sun, of the rain, the Metropolis of the Amazon. Women and men moved about the city, and their sound and noises could be heard by the dwellers, delimiting territories and allowing themselves to be seen daily in the town. At night, the streets and squares were invaded by the sounds and songs of the bohemian and serenading musicians, and an idealized and romantic representation of these subjects was elaborated by the modernist intellectuals that participated in it. However, bohemia was not restricted to serenading groups; other bohemian practices could also be lived in closed spaces. While the elites continued attached to the aesthetic values of the Belle Époque, considering the classical music as the true musical art, a multiplicity of sounds, rhythms and timbres could be heard in the town and was criticized as popular and distorting of the true musical art. The songs, produced in their majority for teatro de revista [Brazilian cabaret], told and sang about political, economic and social problems faced by the common people. Gentil Puget, member of a generation of musicians of classical background imbued of the modernist ideals, incorporated the popular and the regional to his artistic production, seeking to build a music that was intended as delimiting the regional and national identity